The Effect of KineMaster Learning Videos and Learning Styles on the Results of Learning to Write Negotiation Texts for Senior High School Students - Ernawati Ernawati; Atmazaki Atmazaki (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to explain and analyse the effect of KineMaster learning videos and learning styles on the learning outcomes of writing negotiating texts for the tenth grade of state Madrasah Aliyah in Lima Puluh Kota. This type of research is a quantitative research using a quasi-experimental method with a factorial design or factorial design (2x2). Data collection techniques were writing tests of negotiating texts. The research sample was taken using a purposive sampling technique. Data analysis was carried out descriptively by testing normality, homogeneity, and hypothesis testing. The results showed 3 things. First, learning through KineMaster learning videos is better than teaching through videos sourced from Youtube. Second, there is a significant difference between the results of learning to write negotiating texts between students who are grouped with learning styles and students who are not grouped with learning styles. Third, there is a significant interaction between KineMaster learning videos and learning styles on the results of writing negotiating texts. Therefore, it can be concluded that KineMaster learning videos and learning styles affect students' learning outcomes in writing negotiating texts.